Predictive factors of the interruption of exclusive breastfeeding in premature infants: a prospective cohort - Lucyana Silva Luz; Ruth Minamisava; Carmen Gracinda Silvan Scochi; Ana Karina Marques Salge; Laiane Medeiros Ribeiro; Thaíla Corrêa Castral
ABSTRACT Objective: to evaluate the incidence of exclusive breastfeeding and the risk factors associated to its interruption in premature infants after hospital discharge. Method: this is a prospective cohort with 113 premature infants in a neonatal unit, whom were followed-up from 7 to 15 days after hospital discharge. The outcome was the interruption of exclusive breastfeeding. Maternal and neonatal exposure variables were evaluated by a regression model and described by the confidence interval (95%) and risk ratio. Results: exclusive breastfeeding rate was 81.4% at discharge and 66.4% at 7 to 15 days after discharge. Double gestation, time of mechanical ventilation and birth weight were associated with higher risks of interruption of exclusive breastfeeding after discharge. Conclusion: there is a need for the implementation of actions that promote the early onset and maintenance of exclusive breastfeeding of premature infants.